Haji Pengabdi Setan: Ali Mustafa Yaqub and The Contextual Understanding of The Hadith - Ubet, Abdulloh (Department of Qur'an dan Hadith Faculty of Ushuluddin and Philosophy UIN Sunan Ampel Surabaya, 2022)
Abstract: This article examines Ali Mustafa Yaqub’s thoughts in the framework of contextual understanding of the hadiths. As a scholar, Yaqub actively writes many articles in the mass media and frequently directs his critics by using hadith as a means for criticism. This article analyzes his opinion regarding the excessive ḥajj and ‘umrah conducted by Indonesian Muslim community. Yaqub is of the opinion that excessive ḥajj and ‘umrah have changed the law from what was originally obligatory and sunna to makrūh or even forbidden (ḥarām), because they should prioritize social obligations such as helping orphans and the poor. Yaqub’s argument is set forth in his controversial book entitled Haji Pengabdi Setan. This study observes how Yaqub draws legal conclusions. This article finds that Yaqub takes his opinion from the concept of fiqh al-awlawīyāt proposed by Yūsuf al-Qarḍāwī. This method is called ijmālī, namely understanding the meaning of hadith textually and partially rather than contextual and comprehensive analysis. In conclusion, this study also finds that Yaqub’s method of understanding hadith is different from previous hadith experts and seems to be less accurate in his reasoning.